Cloning and expression of a structural gene from Chlorobium vibrioforme that complements the hemA mutation in Escherichia coli. - Avissar, Y J (1990)
Escherichia coli SASX41B carries the hemA mutation and requires delta-aminolevulinic acid for growth. Strain SASX41B was transformed to prototrophy with pYA1, a plasmid vector carrying a 5.8-kilobase insert of genomic DNA from the green sulfur bacterium Chlorobium vibrioforme. Cell extracts prepared from transformed cells are able to catalyze transfer of label from [1-14C]glutamate or [3,4-3H]glutamyl-tRNA to delta-aminolevullinic acid at rates much higher than extracts of wild-type cells can, whereas extracts prepared from untransformed strain SASX41B cells lack both activities. By comparing the relative abilities of glutamyl-tRNAs derived from several heterologous cell types to function as substrates for the dehydrogenase reaction in extracts of HB101 and SASX41B cells transformed by pYA1, it was determined that the expressed dehydrogenase in the transformed cells resembled that of C. vibrioforme and not that of E. coli. Thus it can be concluded that plasmid pYA1 contains inserted DNA that codes for a structural component of C. vibrioforme glutamyl-tRNA dehydrogenase which confers glutamyl-tRNA substrate specificity.